Prototype Aplikasi Interaktif sebagai Media Revitalisasi Artefak Masjid Agung Demak - Mustagfirin Mustagfirin; Toto Haryadi; Dwi puji prabowo (Jurnal Informatika Upgris, 2019)
Indonesia is known as a country which has a lot of physical cultures namely artifacts. In Central Java, artifacts based on religius are often found in Demak, as a Islamic civilization center in Java island. Demak is known as “Kota Wali” has various artifacts which stored in museum with condition such as damage, broken, cracked, missing writing, and so on. This become problem in introducing them to the youth. On the other hand, they prefers play gadgets like smartphone rather than visit museum. Bases on these, authors design revitalization media of Demak Geat Mosque’s artifacts digitally. This research use qualitative method with observation and literature study techniques, the revitalization media is designed use design thinking method to produce prototype of interactive application which can be accessed through smartphone. The result of this research is prototype which presents information about Demak Great Mosque’s artifacts, which is expected to be an educational media for introducing them to the youth. Keywords—application, artifacts, Demak, Design Thinking